Trend of stillbirths and neonatal deaths in University Kebangsaan Malaysia Medical Centre (UKMMC) from 2004- 2010. - Haslina Hassan,; Rosnah Sutan,; Nursazila Asikin Mohd Azmi,; Shuhaila Ahmad,; Rohana Jaafar, (Universiti Kebangsaan Malaysia, 2013)
The aim of the Fourth Millennium Developmental Goal is to reduce mortality among children less than 5 years by two thirds between 1990 and 2015. Efforts are more focus on improving children’s health. The aim of this study was to describe the trend of stillbirth and neonatal deaths in University Kebangsaan Malaysia Medical Centre from 2004 to 2010.